Neurodevelopmental outcome in children between one and five years after persistent pulmonary hypertension of term and near-term newborns - Atlan, Laetitia; Berthomieu, Lionel; Karsenty, Caroline; Gascoin, Géraldine; Arnaud, Catherine; Breinig, Sophie (Frontiers in Pediatrics, 2024)
Background Persistent pulmonary hypertension of the newborn (PPHN) is a serious condition that affects 1–2 per 1,000 newborns. Scientific data report the existence of neurological developmental abnormalities between 10 and 30%, but the description of these disorders linked with this situation of cerebral hypoxia and haemodynamic failure remains poorly documented. Objective The main goal of this study was to describe the prevalence of neuro-psychomotor developmental disorders in children aged between one and five years old who have been hospitalised at birth in a neonatal intensive care unit for the management of PPHN. Methods All of the newborns ≥34 weeks of gestational age (WGA) with PPHN, treated with inhaled nitric oxide in our neonatal intensive care unit between January 2015 and December 2019 were retrospectively enrolled. An ASQ-3 standardised questionnaire, adapted to the appropriate age (12, 24, 36, 48 and 60 months) was performed by the parents. Results Fifty-five children (81% of answers) with a median age of 36 months (11–68), whose real age was close to the one of the questionnaire (12, 24, 36, 48 and 60 months), have been included in this study. There was 47% of pathological score [borderline: less than 1 standard deviation (SD) or suspect: less than 2SD] in at least one of the five studied domains, mainly in communication (25%) and individual and social skills (22%), despite a high overall score of 250 [220; 285] out of 300 that improved with age. Conclusion This study showed a significant prevalence of neuro-psychomotor developmental disorders which justifies making more accessible a prolonged and adapted follow-up for early and multidisciplinary screening and management of these children with PPHN history. Larger cohorts are needed to better explore long term outcome of these vulnerable term neonates.